Mycotoxin occurrence in kernels and straws of wheat, barley, and tritordeum - Marco Gozzi; Massimo Blandino; Renato Bruni; Luca Capo; Laura Righetti; Chiara Dall’Asta (Mycotoxin Research, 2024)
Thirty-two varieties of common and durum wheat, hordeum, barley, and tritordeum collected over two harvesting years (2020 and 2021) were investigated for the presence of multiple Fusarium -related mycotoxins in asymptomatic plants. DON, 3-AcDON, 15-AcDON, T-2, HT-2, and ZEN together with the emerging mycotoxin ENN B and the major modified form of DON, namely DON3Glc, were quantified by means of UHPLC-MS/MS. Overall, DON and ENN B were the most frequently detected mycotoxins, albeit large inter-year variability was observed and related to different climate and weather conditions. Straws had higher mycotoxin contents than kernels and regarding DON occurrence tritordeum was found to be the most contaminated group on average for both harvesting years, while barley was the less contaminated one. Emerging mycotoxin ENN B showed comparable contents in kernels compared to straw, with a ratio close to 1 for tritordeum and barley. Regarding the occurrence of the other evaluated mycotoxins, T-2 and HT-2 toxins have been spotted in a few tritordeum samples, while ZEN has been frequently found only in straw from the harvesting year 2020. The data collected confirms the occurrence of multiple Fusarium mycotoxins in straws also from asymptomatic plants, highlighting concerns related to feed safety and animal health. The susceptibility of Tritordeum, hereby reported for the first time, suggests that careful measures in terms of monitoring, breeding, and cultural choices should be applied when dealing with his emerging crop.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

How Lactobacillus plantarum shapes its transcriptome in response to contrasting habitats - Pasquale Filannino; Maria De Angelis; Raffaella Di Cagno; Giorgia Gozzi; Ylenia Riciputi; Marco Gobbetti (Environmental Microbiology, 2018)
Summary Triplets of Lactobacullus plantarum strains were isolated from nine contrasting habitats. Without any passage through other culture media, isolation and cultivation were on model media that strictly reproduced the chemical and physical conditions and stressors of the habitats of origin. Here, we demonstrated how L. plantarum regulates and shapes its transcriptome in response to contrasting habitats. Firstly, multivariate clustering analysis of transcriptional data (RNA‐Seq), complemented with metabolomics and phenomics, grouped the strains according to the habitats of origin. Subsequently, selected strains from each habitat switched to repeated cultivation on MRS medium and transcriptomes homogenized into a unique cluster. Adaptation to this common medium mainly relied on activation of genes for phage‐ and prophage‐related proteins and transposases. Finally, the comparison of growth across model media and with respect to MRS medium showed that 44% of the overall 3112 gene transcripts changed depending on the specific habitat. Regulation and shaping of transcriptomes mainly concerned carbohydrate acquisition, pyruvate catabolism, proteolytic system and amino acid, lipid and inorganic ion transport and metabolism, with contrasting responses for contrasting habitats. Pathways reconstruction demonstrated how the large genome size of L. plantarum imparts transcriptome and metabolic flexibility as the basic mechanism for a nomadic lifestyle.